2012
DOI: 10.1002/mame.201200331
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Stability of Fibers Electrospun from Peptides with Ionized Side Chains

Abstract: Non‐woven electrospun fiber mats made of polypeptides are increasingly considered attractive for basic research and technology development in the life sciences, medicine, and other areas. Here, co‐poly(L‐glutamic acid4, L‐tyrosine1) (PLEY) was adopted as a model polymer for a study of the mechanisms of fiber stability. Crosslink density has been quantified by a dye‐based method. Fiber morphology, elemental composition, and stability have been assessed by microscopy and energy‐dispersive X‐ray spectroscopy (EDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Apart from self-assembly peptides that are known to aggregate into supramolecular fiber structures through hydrophobic interactions, hydrogen bonds, electrostatic interactions, and van der Waals interactions, , synthetic polypeptides can also be electrospun into typical fibrous meshes . Research has showed that many characteristics of electrospun polypeptides such as their stability in aqueous media, hydrophobicity, and photoresponsivenes as well as their more bioactive features, for example, their protein adsorption, could be tuned via amino acid content and sequence. When spun alone, polypeptide fibers are often further cross-linked via EDC or aldehyde chemistry.…”
Section: Fabrication Of Bioactive Electrospun Fibersmentioning
confidence: 99%
“…Apart from self-assembly peptides that are known to aggregate into supramolecular fiber structures through hydrophobic interactions, hydrogen bonds, electrostatic interactions, and van der Waals interactions, , synthetic polypeptides can also be electrospun into typical fibrous meshes . Research has showed that many characteristics of electrospun polypeptides such as their stability in aqueous media, hydrophobicity, and photoresponsivenes as well as their more bioactive features, for example, their protein adsorption, could be tuned via amino acid content and sequence. When spun alone, polypeptide fibers are often further cross-linked via EDC or aldehyde chemistry.…”
Section: Fabrication Of Bioactive Electrospun Fibersmentioning
confidence: 99%
“…[8] Shin and co-workers illustrate how an electrospun fibrous mesh can be combined with a cell-adhesive peptide via a bio-inspired immobilization process, [9] and Haynie and coworkers describe a model for the stability of electrospun fiber mats made of polypeptides in aqueous media. [10] Son and co-workers introduce a functional silver-polydopamine coating of electrospun polymer nanofibers through the oxidation of dopamine and the related reductive potentials for metal ions. [11] Hyun and co-workers describe a new method for preparing mesoporous polymer-nanoparticle composites containing a large amount of magnetic nanoparticles.…”
Section: Il-doo Kimmentioning
confidence: 99%